Who are 'Multi-Helpers'? Profile of Older Adults Engaging in Multiple Help-Giving Activities - Hämäläinen Hans; Tanskanen Antti O; Danielsbacka Mirkka (Springer, 2023)
This study considers older adults providing multiple types of support toward different parties in both public and private domains, referred to as 'multi-helpers'. Although individuals involved in multiple help-giving activities can be important actors at individual, community, and societal levels, few studies have evaluated their characteristics. Using population-based data for older Finns (n = 2,174) we explored the profiles of multi-helpers for provision of: (1) instrumental help to friends and relatives; (2) financial aid to friends and relatives; (3) volunteering; and (4) charitable giving. Of the respondents, 75% provided instrumental help, 44% provided financial aid, 21% participated in volunteering, and 58% made charitable donations. Overall, 7% were considered multi-helpers, as they were engaged in providing all four types of support. Having a partner, being a widow, having a higher level of education, living in rural area, being religious, and having a larger number of friends increased the probability of being a multi-helper. The findings are interpreted in light of opportunity structures and role extension approaches.